2013
DOI: 10.1186/2045-3701-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion venom peptide SPVII promotes irradiated cells proliferation and increases the expression of the IL-3 receptor

Abstract: BackgroundThe previous investigation demonstrated the radioprotective efficacy of peptides isolated from the venom of Buthus Martti Karsch. In this study, the effect of isolated scorpion venom peptide II (SVPII) on irradiated M-NFS-60 cells and mouse bone marrow mononuclear cells (BM-MNCs) was observed. The AlamarBlue cell viability assay, a colony-forming unit (CFU) assay, flow cytometry (FCM), immunofluorescence, and Western blotting were used to evaluate cell proliferation, cell cycle progression, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…SVPII augments the proliferation of these cells in a concentration-dependent manner (12). The results of the present study demonstrated that the principal component in the SVPII, namely SVP-B5, promotes the proliferation of the M-NFS-60 mouse-derived myelocytic leukemia cell line.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…SVPII augments the proliferation of these cells in a concentration-dependent manner (12). The results of the present study demonstrated that the principal component in the SVPII, namely SVP-B5, promotes the proliferation of the M-NFS-60 mouse-derived myelocytic leukemia cell line.…”
Section: Discussionsupporting
confidence: 61%
“…A recent study by our group identified SVP-B5, a novel peptide from the SVPII, which mitigates radiation-induced DNA damage and improves the survival rate through the reactive oxygen species-p16/p21 pathway (10). In another study by our group, hematopoietic growth factor-like effects of SVPII were reported (12). The present study demonstrated that the principal component of SVPII, namely SVP-B5, promotes the proliferation of irradiated hematopoietic cells.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations